Enhancing energy migration upconversion through a migratory interlayer in the core–shell–shell nanostructure towards latent fingerprinting. Issue 36 (7th September 2020) - Wang, Xixi; Yan, Long; Liu, Songbin; Zhang, Peng; Huang, Rong; Zhou, Bo
Abstract : A mechanistic strategy to enhance energy migration upconversion (EMU) of lanthanides (Dy 3+, Sm 3+, Nd 3+, Eu 3+, Tb 3+ ) has been constructed by designing a migratory NaGdF4 interlayer in the EMU model. Abstract : Mechanistic studies on photon upconversion play a critical role in the fundamental research of the luminescence of rare earth ions as well as their emerging applications. Energy migration mediated upconversion (EMU) has recently shown to be an important model for the photon upconversion of the lanthanide ions without the intermediate states. However, the EMU process is complex and there is seldom work regarding the interactions in the core–shell interfacial area that may impose a quenching effect on the resultant upconverison. Here, we report a strategy to enhance the upconversion luminescence by inserting a migratory NaGdF4 interlayer in the EMU model to minimize the unwanted quenching processes in the interfacial area. The design of a NaGdF4 :Yb/Tm@NaGdF4 @NaGdF4 :A (A = Dy, Sm, Nd, Eu, Tb) core–shell–shell nanostructure indeed leads to an enhancement of photon upconversion under 980 nm excitation. The details of the interfacial quenching processes between the Tm 3+ in the core and the emitters in the shell were investigated. Moreover, these optimized upconversion nanoparticles can be used in the multicolor latent fingerprint recognition with the secondary fingerprint details easily achievable, showing great potential in the anti-counterfeiting of fingerprints for information security.